Make it matter : how managers can motivate by creating meaning - Mautz, Scott (AMACOM -- American Management Association, 2015)
How many people find a sense of purpose in their jobs? Unfortunately, studies show that most do not. Their bodies may put in long hours, but their hearts and minds never punch in. And that's a terrible dilemma for organizations trying to motivate their workforces to do more with less. Make It Matter is the antidote to crisis levels of disengagement. This upbeat, original book shows how meaning-rich workplaces connect, inspire, and catapult employees into new realms of productivity and well-being.